Risk analysis of applying improved agricultural technologies in Gedaref rain-fed sector of eastern Sudan (1990-2004) - Mustafa, Rajaa; Elgali, Mohamed; Kuhlmann, F (Gezira Journal of Agricultural Science; Vol 9 No 2 (2011), 2011)
It is argued that the adoption of recommended improved technology in the Gedaref area can increase farm income while diversification by introducing sheep and gum arabic enterprises to sorghum monoculture of the Gedaref may lead to farm income stability. Under these arguments in favor of diversification and the use of improved technology, this research work aims mainly at studying and analyzing the performance of the mechanized rain-fed sector of Gedaref under uncertainty. Specifically, the study has evaluated different production strategies in terms of risk efficiency under the proposed improved cultural practices. The study mainly applies a stochastic budgeting approach to evaluate the proposed production strategies under improved cultural practices. The stochastic budgeting simulation is done by using @ Risk software that allows the representation of uncertainty as probability distributions and then performs stochastic simulation using Latin Hypercube technique and the results are then given also as probability distributions. By applying the strategies of improved practices, farmer’s chance to lose at the end of the planning period is very small. The Cumulative Distribution Functions (CDFs) graphs and the statistics generated from the stochastic simulation for the strategies under improved practices showed that, they are the dominant alternatives in terms of risk efficiency in a first degree sense i.e. they are preferable for a wide range of farmers’ absolute risk aversion level (+∞ > r a <-∞). The results of comparing the distribution of each strategy within improved practices indicated that the application of the improved technological packages has a positive impact in maintaining income stability in all investigated strategies.    تنطوي ممارسة الأعمال الزراعية دائماً علي المخاطر، مما دعى إلى ضرورة الأخذ بالاعتبار المخاطر التي تواجه الأعمال الزراعية عند التخطيط لها. تشير الدراسات إلى أن تبني التقنيات الزراعية تؤدى إلى زيادة الدخل ، كما أن تنويع  التركيبة المحصولية بإدخال الإنتاج الحيواني ومحصول الصمغ العربي يؤدى إلى استقرار الدخل الزراعي في حالة الزراعة الآلية بمنطقة القضارف. في ظل هذه المعطيات تهدف هذه الدراسة إلى تحليل ودراسة أداء العمل الزراعي في منطقة الزراعة الآلية بالقضارف تحت الظروف الحالية. ولقد قامت هذه الدراسة بتقييم استراتيجيات زراعية مختلفة في ظل التقنيات الحديثة المقترحة تحت ظروف المخاطر. وذلك باستخدام طريقة الميزانية الاحتمالية لتقييم الإستراتيجيات الزراعية المختلفة. استخدمت الميزانية الاحتمالية كأداة رئيسية في هذا التحليل كما استخدم أسلوب المحاكاة لهذه الإستراتيجيات بواسطة توزيع لاتين هايبركيوب للتوزيعات الاحتمالية والتي تعرض النتائج في صورة منحنيات الدوال التوزيعية التراكمية. أوضحت النتائج انه عند تطبيق التقنيات الحديثة فإن فرص خسارة المزارعين عند نهاية الفترة التخطيطية ستكون قليلة، كما أوضحت منحنيات الدوال التوزيعية التراكمية أن استراتيجيات التقنيات الحديثة تسود على التقنيات التقليدية الأخرى من ناحية كفاءتها في تقليل الأخطار كما أوضحت تفضيلها في مدى واسع من مقياس المزارعين المتجنبين للمخاطر. كما أوضحت نتائج مقايسات التوزيعات الاحتمالية لكل استراتيجيه على حده أن التقنيات الحديثة لها المقدرة على العمل على استقرار دخول المزارعين في جميع الاستراتيجيات المدروسة.